Protein engineering of the tissue inhibitor of metalloproteinase 1 (TIMP-1) inhibitory domain. In search of selective matrix metalloproteinase inhibitors. - Wei, S; Chen, Y; Chung, L; Nagase, H; Brew, K (2003)
Studies of the structural basis of the interactions of tissue inhibitors of metalloproteinases (TIMPs) and matrix metalloproteinases (MMPs) may provide clues for designing MMP-specific inhibitors. In this paper we report combinations of mutations in the major MMP-binding region that enhance the specificity of N-TIMP-1. Mutants with substitutions for residues 4 and 68 were characterized and combined with previously studied Thr(2) mutations to generate mutants with improved selectivity or binding affinity to specific MMPs. Some combinations of mutations had non-additive effects on DeltaG of binding to MMPs, suggesting interactions between subsites in the reactive site. The T2L/V4S mutation generates an inhibitor that binds to MMP-2 20-fold more tightly than to MMP-3(DeltaC) and over 400-fold more tightly than to MMP-1. The T2S/V4A/S68Y mutant is the strongest inhibitor for stromelysin-1 among all mutants characterized to date, with an apparent K(i) for MMP-3(DeltaC) in the picomolar range. A third mutant, T2R/V4I, has no detectable inhibitory activity for MMP-1 but is an effective inhibitor of MMP-2 and -3. These selective TIMP variants may provide useful tools for investigation of biological roles of specific MMPs and for possible therapy of MMP-related diseases.